Analytical modelling and characterisation of an infrasound generator in the air. (May 2019) - Vincent, P.; Larsonnier, F.; Rodrigues, D.; Durand, S.
Abstract: This paper presents an accurate characterisation based on an experimental set-up and mathematical models of a dynamic pressure infrasound generator. The Commissariat à l'énergie atomique (CEA) has developed microbarometers to measure infrasound waves in the atmosphere. To characterise its sensors and validate their requirements, an infrasound generator has been designed, which covers a frequency range from 4.0 10 −4 Hz to 300 Hz. This pressure generator still needs accurate characterisation as there is no standard reference in the infrasound frequency range for such sensor calibration. The research focused on 17 parameters that affect the behaviour of this infrasound pressure generator. Two analytical models of the sound pressure in the cylindrical cavity of the calibrator are presented. An experimental characterisation was also performed to adjust the model parameters with genetic algorithms to the measurements, and the results of the comparison between the measurements and the models are discussed. This study highlights the influence of the thermodynamic transition from isothermal to adiabatic transformation and the influence of viscoelastic non-linearities of a loudspeaker membrane. It aims to characterise the amplitude and phase responses of the generator in order to develop an improved infrasound calibration device for microbarometers with a similar technology.